2003
DOI: 10.21273/hortsci.38.6.1117
|View full text |Cite
|
Sign up to set email alerts
|

`Umatilla Russet' and `Russet Legend' Potato Yield and Quality Response to Irrigation

Abstract: `Umatilla Russet' and `Russet Legend', two newly released potato (Solanum tuberosum L.) cultivars were compared with four established cultivars (`Russet Burbank', `Shepody', `Frontier Russet', and `Ranger Russet'). Potatoes were grown under four, season-long, sprinkler irrigation treatments in three successive years (1992-94) on silt loam soil in eastern Oregon. At each irrigation, the full irrigation treatment received up to the accumulated evapotranspiration (ETc<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Precise irrigation of potato has been closely related to many tuber quality attributes (Shock et al, 2007a). The ideal irrigation criteria for potato on silt loam is often wetter (25 to 30 kPa) where drip irrigation is applied frequently (Kang et al, 2004;Shock et al, 2002c;Wang et al, 2007b) than where sprinkler or furrow irrigations systems are used (50 to 60 kPa) (Eldredge et al, 1992(Eldredge et al, , 1996Shock et al, 1993Shock et al, , 1998bShock et al, , 2003Shock et al, , 2007a. Wetter irrigation criteria are needed on sandy soils than on silt loam soils.…”
Section: Crops Respond Differently To Soil Water Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise irrigation of potato has been closely related to many tuber quality attributes (Shock et al, 2007a). The ideal irrigation criteria for potato on silt loam is often wetter (25 to 30 kPa) where drip irrigation is applied frequently (Kang et al, 2004;Shock et al, 2002c;Wang et al, 2007b) than where sprinkler or furrow irrigations systems are used (50 to 60 kPa) (Eldredge et al, 1992(Eldredge et al, , 1996Shock et al, 1993Shock et al, , 1998bShock et al, , 2003Shock et al, , 2007a. Wetter irrigation criteria are needed on sandy soils than on silt loam soils.…”
Section: Crops Respond Differently To Soil Water Tensionmentioning
confidence: 99%
“…Hybrid poplar tree (Populus deltoides • P. nigra) growth was measured with variable SWT on silt loam in semiarid eastern Oregon (Shock et al, 2002a). Rooting was mostly in the 0-to 30-cm layer and SWT Eldredge et al, 1992Eldredge et al, , 1996Shock et al, 1998bShock et al, , 2003 Oregon Silt loam Furrow GMS 20 cm Shock et al, 1993 Table 3. Soil water tension (SWT) as irrigation criteria for cole crops (Brassica spp.).…”
Section: Other Field and Vegetable Cropsmentioning
confidence: 99%
“…The new cultivars Umatilla Russet and Russet Legend are much less susceptible to sugar ends than Russet Burbank (Mosley et al 2000a,b). Umatilla Russet is more subject to loss of yield following water stress than Russet Burbank and Legend Russet is at least as susceptible to water stress induced yield losses as Russet Burbank (Shock et al 2003). No research has been conducted to determine if the ability to produce and transport assimilates under stress conditions also imparts resistance to sugar ends.…”
Section: Future Research Needsmentioning
confidence: 99%
“…, in Albacete of Spain, reported that irrigation water requirement was 597 mm for maximum tuber yield of 45.18 t ha −1 using drip irrigation. In many instances of research , seasonal evapotranspiration of potato ranged from 350 mm to 800 mm, depending on the climate and growing conditions. Unlu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Faberio et al [45], in Albacete of Spain, reported that irrigation water requirement was 597 mm for maximum tuber yield of 45.18 t ha 21 using drip irrigation. In many instances of research [45][46][47][48][49][50], seasonal evapotranspiration of potato ranged from 350 mm to 800 mm, depending on the climate and growing conditions. Unlu et al [51] found that seasonal water use in potato varied between 565 and 830 mm, depending on the irrigation regime in Middle Anatolian and Ni gde-Nevşehir provinces of Turkey-conditions where drip irrigation methods were used.…”
Section: Water Use and Potato Yieldmentioning
confidence: 99%